Ash Cenosphere from Solid Fuels Combustion. Part 1: An Investigation into Its Formation Mechanism Using Pyrite as a Model Fuel - Li, Yi; Wu, Hongwei (American Chemical Society, 2012)
This paper reports a systematic investigation into the fundamental formation mechanism of ash cenosphere during solid fuels combustion using pyrite as a model fuel. The combustion of pulverized pyrite particles (38-45 µm) was carried out in a laboratory-scale drop-tube furnace at furnace temperatures of 530-1100 °C. The formation of ash cenosphere commences at 580 °C. At temperatures = 600 °C, the ash products of pyrite combustion consist of dominantly large ash cenospheres (up to 130 µm in diameter) with thin shells (1-3 µm) and ash cenosphere fragments of various sizes. An increase in the temperature results in enhanced ash cenosphere fragmentation. The formation of molten Fe-S-O droplets during pyrite combustion is essential to ash cenosphere formation. The Fe-S-O melts inflate and expand into cenospheric forms (that may also burst intosmaller fragments) via sulfur oxide gas generation inside the molten droplets as oxidation reactions progress. Further oxidation and resolidification transforms these cenospheric precursors into final ash cenospheres that also experience fragmentation and contain dominantly iron oxides.